Experimental study and numerical modeling of the thermal performance of cold rooms for storage of meat products - Campos, Rodrigo (2013)
This paper contributes to the energy efficiency and thermal performance improvement in cold rooms used for conservation and storage of meat products, commonly used in the agro industrial sector. An experimental analysis of the thermal performance of a cold room in the Covilhã region (Portugal) is developed, verifying its external conditions and construction parameters. A steady state 3D CFD model of the cold room is developed, allowing the detailed evaluation of the airflow and heat transfer. The CFD model setup required the definition of a physical-mathematical model based on the equations of continuity, momentum and energy. The comparison of numerical and experimental results allowed the validation of the CFD model. Thus, a parametric study is developed, which consists in changing the boundary condition values at the discharge grilles of evaporators. The parametric predictions show that the cold system, for product loading defined on the experimental analysis, is oversized, thus enabling the modification of the discharge air temperature and velocity. In this modification, the energy consumption is reduced maintaining similar thermal performance and ensuring the food safety. Thus, it is predicted an improvement of the energy efficiency and a consequent savings of environmental resources, energy and financial resources.